1979
DOI: 10.2170/jjphysiol.29.691
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac Sympathetic Nerves in Rats: Anatomical and Functional Features

Abstract: 1. Anatomical pathways and natures of reflex as well as spontaneous activities of cardiac sympathetic nerves (CNs) were investigated in rats. 2. Anatomically, the stellate CNs on both sides provide a major sympathetic supply to the rat heart with additional contribution of the thoracic CNs on the left side. 3. Functions of these CNs were studied in chloralose-urethane anesthetized and artificially ventilated rats. Electrical stimulation of these CNs produced an increase in heart rate and a rise in blood pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

1984
1984
2006
2006

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 29 publications
3
4
0
Order By: Relevance
“…It is noteworthy that the time course of heart rate response to IOR/R stimulation was longer than that of cardiac sympathetic nerve activity. This finding was supported by the report of Yasunaga and Nosaka (1979) [9] that an electrical stimulation of the cardiac sympathetic nerve produced a tachycardiac response that continued long after stimulation.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…It is noteworthy that the time course of heart rate response to IOR/R stimulation was longer than that of cardiac sympathetic nerve activity. This finding was supported by the report of Yasunaga and Nosaka (1979) [9] that an electrical stimulation of the cardiac sympathetic nerve produced a tachycardiac response that continued long after stimulation.…”
Section: Discussionsupporting
confidence: 64%
“…Furthermore, heart rate response was also much larger when the stimulus was delivered to the right elbow joint, as opposed to left, in spinalized rats. A laterality of the heart rate response to noxious cutaneous stimulation in spinalized rats has previously been reported by Kimura et al (1995) [5], and this phenomenon was suggested to be a reflection of the influence of cardiac sympathetic nerves on the right side of the heart, particularly those that innervate the sinus node [7][8][9][10] (Fig. 9).…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…Electrical stimulation of the cardiac sympathetic nerve is shown here in the mouse to increase HR, as shown previously in the other species (Liddell & Sherrington, 1929; Yasunaga & Nosaka, 1979). Following a period of sympathetic stimulation in the mouse, there is a prolonged attenuation of subsequent cardiac vagal activity.…”
Section: Discussionsupporting
confidence: 87%
“…Since the influence of the right cardiac sympathetic nerve on sinus rhythm is greater than that of the left cardiac sympathetic nerve [10], recordings were made from the right nerve. With the rats in a prone position, the cardiac sympathetic nerves were dissected free following the removal of the second costal bone, as described previously [11,12], and their neuronal activity was amplified using a preamplifier (time constant 0.01 s; S-0476, Nihon Kohden, Tokyo) and sampled using an analog-to-digital converter (PowerLab/8, AD Instruments, Australia) at a rate of 2,000 samples/s that was rectified and integrated every 5 s. The signal recorded at the end of the experiment (after the rat had died) was set as the background noise.…”
Section: Methodsmentioning
confidence: 99%